Gender socioeconomic inequalities in intimate relationships introducing the GSEI index - Klasnić, Ksenija, sociologinja (2020)
Inspired by the materialist feminist theoretical approach, this study starts from an underlying assumption that research of gender socioeconomic inequalities in intimate relationships requires the analysis of specific variables that constitute the socioeconomic status of intimate partners. Based on five indicators relevant for contemporary Croatian society, the GSEI index was constructed and applied to a representative sample of Croatian women in intimate relationships. The results showed significant gender socioeconomic inequalities between intimate partners, mostly in favour of men. The highest level of inequality between intimate partners was discovered with regard to real-estate ownership, whereas the highest level of equality between partners was found in their level of education. Although socioeconomic inequalities between intimate partners in favour of men prevail regardless of the geographic and social context, they are more pronounced in regions with more traditional values, among couples who live in rural areas, and among those who are married (in comparison with those who live in domestic partnership). A recommendation for further research and GSEI index application is to consider which are the relevant indicators for measuring gender socioeconomic inequalities in intimate relationships depending on the wider social context.
Inspirirana materijalističkim feminističkim teorijskim pristupom, ova studija polazi od temeljne pretpostavke da istraživanje rodnih socioekonomskih nejednakosti u intimnim vezama zahtijeva analizu specifičnih varijabli za mjerenje socioekonomskog statusa intimnih partnera. Na temelju pet pokazatelja relevantnih za suvremeno hrvatsko društvo, konstruiran je GSEI indeks i primijenjen na reprezentativnom uzorku žena u intimnim vezama u Hrvatskoj. Rezultati su pokazali značajne rodne socioekonomske nejednakosti među intimnim partnerima, uglavnom u korist muškaraca. Najviša razina nejednakosti među intimnim partnerima utvrđena je u vlasništvu nekretnina, dok je najniža razina nejednakosti među partnerima utvrđena kod razine obrazovanja. Iako socioekonomske nejednakosti među intimnim partnerima u korist muškaraca prevladavaju bez obzira na geografski i društveni kontekst, one su izraženije u regijama s tradicionalnijim vrijednostima, među parovima koji žive u ruralnim područjima i onima koji su u braku (u usporedbi s onima koji žive u izvanbračnim zajednicama). Preporuka za daljnja istraživanja i primjenu GSEI indeksa jest da je potrebno uzeti u obzir koji su relevantni pokazatelji za mjerenje socioekonomskih nejednakosti u intimnim odnosima, ovisno o širem društvenom kontekstu.
Bilješke uz tekst.
Bibliografija: str. 372-374.
Abstract ; Sažetak.
Keywords: Ekonomske nejednakosti -- Rodne nejednakosti -- Intimne veze -- Socioekonomski status -- GSEI indeks